Dynamic stochastic general equilibrium (DSGE) priors for Bayesian vector autoregressive (BVAR) models: DSGE model comparison - Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2007)
This Paper describes a procedure for constructing theory restricted prior distributions for BVAR models. The Bayes Factor, which is obtained without any additional computational e?ort, can be used to assess the plausibility of the restrictions imposed on the VAR parameter vector by competing DSGE models. In other words, it is possible to rank the amount of abstraction implied by each DSGE model from the historical data.
Keywords: C11; C13; C32; C52; 330; BVAR; DSGE Model Evaluation; Gibbs Sampling; Bayes Factor; Dynamisches Gleichgewicht; VAR-Modell; Bayes-Statistik; Theorie